PERSONALITY ARGUMENTATION TOOLBOX - Gerasimova Borissova , Lalka (Revista Inclusiones, 2021)
Persuasiveness is one of the most important skills that can and should be acquired, as this skill is useful in numerous situations. The ability to persuade and influence others can be the best tool for achieving planned goals and agreement. The best benefit of knowing about persuasion techniques in addition to achieving one’s goals will help them understand how marketers and advertisers sell products and services that no one really needs. Persuasion and influence arguments are classified as strong, weak, and untenable. Strong arguments are preferable to counteract interlocutor’s weak ones. The authority of the interlocutor is also important in order to assume their view as correct. Various other techniques for persuasion and influence are also recommended, as means to the same end – to achieve the set goals through influence and persuasion on controversial issues by using strong arguments and authoritative personality.